The distribution of wages in Poland, 1992-2002 - Newell, Andrew; Socha, Mieczyslaw W. (Bonn, 2005)
"This paper analyses the changes in the size distribution of wages in Poland over a decade of transition. Until about 1998 there were some forces tending to increase wage inequality and other forces contracting it. The result was a relatively constant level of inequality. Privatisation was the main force tending to increase wage inequality, partly because it generated major increases in the relative wages of professional and managerial workers. We demonstrate how private firms tend to pay less at the bottom end of the wage distribution and more at the top end. The main force contracting the variance of wages was the decline, between 1992 and 1998 in labour market participation of those with low levels of education. Wage inequality seems to have increased since 2000. Suggestively, whereas privatisation has continued, the decline in participation has halted."